Facilitators and barriers to participation of private sector health facilities in government-led schemes for maternity services in India: a qualitative study. Issue 6 (22nd June 2017) - Yadav, Vikas; Kumar, Somesh; Balasubramaniam, Sudharsanam; Srivastava, Ashish; Pallipamula, Suranjeen; Memon, Parvez; Singh, Dinesh; Bhargava, Saurabh; Sunil, Greeshma Ann; Sood, Bulbul
Abstract : Objective: Despite provision of accreditation of private sector health providers in government-led schemes for maternity services in India, their participation has been low. This has led to an underutilisation of their presence, resources and expertise for providing quality maternal and newborn health services. This study explores the perception of various stakeholders on expectations, benefits, barriers and facilitators to private sector participation in government-led schemes—specifically Janani Suraksha Yojana (JSY)—for maternity service delivery. Design: Narrative-based qualitative study. Face-to-face in-depth interviews were conducted with study participants. The interviews were transcribed, translated and analysed using a reflexive and inductive approach to allow codes, categories and themes to emerge from within the data. Setting: Private obstetricians, government health officials and FOGSI (Federation of Obstetrics and Gynaecological Societies of India) members, Jharkhand and Uttar Pradesh, India. Participants: Eighteen purposefully selected private obstetricians from 9 cities across states of Uttar Pradesh and Jharkhand, 11 government health officials and 2 FOGSI members. Results: The major factors serving as barriers to participation of private practitioners in JSY—which emerged on thematic analysis—were low reimbursement amounts, delayed reimbursements, process of interaction with the government and administrative issues, previous experiences and trust deficit, lack of clarity on the accreditation process and patient-level barriers. On the other hand, factors which were facilitators to participation of private practitioners were ease of process, better communication, branding, motivation of increasing clientele as well as satisfaction of doing social service. Conclusion: Factors such as financial processes and administrative delays, mistrust between the stakeholders, ambiguity in processes, lack of transparency and lack of ease in the process of empanelment of private sector are hindering effective public–private partnerships under JSY. Simplifying and strengthening the processes, communication strategies and branding can help revitalise it.